2019
DOI: 10.1111/jpc.14421
|View full text |Cite
|
Sign up to set email alerts
|

Management of inguinal hernia with prolapsed ovary in very low birthweight infants during neonatal intensive care unit hospitalisation

Abstract: Aim: Prolapsed ovary (PO) in an inguinal hernia (IH) may cause torsion and infarction; however, the management of IH with PO in very low birthweight (VLBW) infants during neonatal intensive care unit (NICU) hospitalisation remains inconsistent. Methods: The medical records of 47 IHs in 30 VLBW infants during NICU hospitalisation between 2008 and 2017 were reviewed retrospectively. Results: Of the 47 IHs, PO was diagnosed in 18 (38.3%). Post-natal age and body weight at diagnosis of IH with PO were 71 (44-172) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
1
0
0
Order By: Relevance
“…In contrast, in the female patients younger than 12 months, the most common hernia content was the ovary, accounting for 90% of cases. Previous studies have shown that IH with a prolapsed ovary was often seen in the first 2 years of life, 17,18 which was supported by the findings of the present study. The ovary must therefore be recognized as the organ most likely to herniate in females, and not the bowel as seen in males.…”
Section: Discussionsupporting
confidence: 92%
“…In contrast, in the female patients younger than 12 months, the most common hernia content was the ovary, accounting for 90% of cases. Previous studies have shown that IH with a prolapsed ovary was often seen in the first 2 years of life, 17,18 which was supported by the findings of the present study. The ovary must therefore be recognized as the organ most likely to herniate in females, and not the bowel as seen in males.…”
Section: Discussionsupporting
confidence: 92%